Mourning Diary: love's work. Issue 2 (23rd February 2016) - Ade, Wernmei Yong
Abstract : The day after his mother's death in 25 October 1977, Barthes began fragments of what would become for readers, as his translator Richard Howard describes, 'a diary only in a rather desperate sense'. As a recording of his intense grief at the passing of his mother, Mourning Diary represents Barthes' last and perhaps his greatest work of love. Reading Barthes' mourning fragments next to his other works written around this time – Roland Barthes, A Lover's Discourse and Camera Lucida – and his final essay 'Deliberations', this paper eschews a reading of Mourning Diary as being about depth and self-disclosure, such as the one offered by Jeremy Berman, whose chapter on Barthes is perhaps one of the earliest, and most sustained, engagements with Barthes' book. I suggest instead that Mourning Diary exemplifies the instance of a writing subject being fully immersed in the signifier. Drawing especially on the figure of the lover in A Lover's Discourse, I argue that Mourning Diary is a simulation of a mourner's discourse, in which the mourning subject stages an utterance that evinces mourning as performative, and the mourner himself a subject always in the process of finding his place in this discourse.